Nodal Na+ and Ca2+ flux dynamics in cortical myelinated axons - Kotler, Oron; Miyazaki, Kenichi; Khrapunsky, Yana; Ross, William N.; Fleidervish, Ilya A. (Frontiers in Cellular Neuroscience, 2025)
Functional neuronal connectivity relies on long-range propagation of action potentials by myelinated axons. This process critically depends on the distribution and biophysical properties of ion channels clustered at specialized, regularly spaced domains, the nodes of Ranvier, where the signals are actively regenerated. Morphological and functional evidence indicates that voltage-gated Na+ channels, which directly support action potential conduction, are exclusively localized at nodes. While these domains also contain voltage-gated Ca2+ channels that contribute to key intracellular signaling cascades, evidence regarding the presence of functional Ca2+ channels in the internodal regions remains conflicting. Using high-speed fluorescence imaging, we characterized action potential–evoked Na+ and Ca2+ dynamics at the nodes of Ranvier in myelinated axons of layer 5 pyramidal neurons in cortical brain slices. Spatially, both Na+ and Ca2+ elevations were largely restricted to the nodal regions. The time-to-peak of the nodal Na+ transients was significantly shorter (3.7 ± 0.3 ms) than that of the Ca2+ transients (10.3 ± 0.6 ms with OGB-1, 4.2 ± 0.5 ms with OGB-5 N), consistent with electrophysiological evidence indicating that Na+ influx occurs primarily during the action potential upstroke, whereas Ca2+ influx predominantly takes place during and after the repolarization phase. The decay of Na+ transients, reflecting lateral diffusion into the internodes, was exceptionally fast in short nodes and became progressively slower in longer ones, consistent with computational models assuming diffusion-based clearance alone. In contrast, Ca2+ transients decayed more slowly and showed no dependence on nodal length, consistent with clearance dominated by active transport. Finally, the post-spike recovery of nodal Na+ fluxes was rapid and temperature-dependent, consistent with the reactivation kinetics of voltage-gated Na+ channels. In contrast, the similarly rapid but temperature-independent recovery of Ca2+ flux suggests that a single action potential does not induce Ca2+ channel inactivation and therefore has minimal impact on their availability during subsequent spikes.